INFRAREDESIGN® as a Way of Individualizing and Protecting the Textile and High Fashion Design - Gršić, Jana Žiljak; Filipović, Korana Gajski; Jurečić, Denis; Žiljak, Vilko (European Journal of Applied Sciences, 2021)
Textile dyeing today includes the observation and creation of graphics, pictures and drawings for two light spectra: visible and near-infrared. In our work, we have developed systems of twin colorants - colors which are the same in the visible spectrum and different in the NIR region. Measurements of light absorbance at 1000 nm (Z) were introduced, since at this wavelength many cameras recognize the intensity of the reflection of daytime sunlight. The planned dyeing of unique clothing that gives extremely different information in the VIS (V) and NIR (Z) spectrum is proposed. In this work, the embedding of a unique hand drawing for the NIR spectrum into a complex computer graphic for the visible spectrum is demonstrated. Dyeing is done with colorants in conventional inkjet printing by producing the planned graphic form Z in the NIR spectrum, invisible to the naked eye. The final product is individualized in its form and protected; it can be detected and its two different states recognized only with dual ZRGB cameras.